Organosilane and Lignosulfonate Stabilization of Roads Unbound: Performance during a Two-Year Time Span - Diego Maria Barbieri; Baowen Lou; Hao Chen; Benan Shu; Fusong Wang; Inge Hoff (Advances in Civil Engineering)
The construction of the new Norwegian E39 highway comprises the excavation of extended tunnelling systems, which lead to a tremendous amount of blasted rocks. Among others, a sustainable cost-benefit application of these resources is represented by their local use as construction material in the unbound layers of the roads. Two types of nontraditional additives are investigated to improve the mechanical properties of aggregates; this is particularly useful for those rocks that do not fulfil the design requirements in their natural status. This work focuses on the field application of two innovative stabilizing technologies based on organosilane and lignosulfonate. The performance of these additive agents is characterized by considering three typical road base layer sections built on purpose according to real practice and added with water (no treatment), organosilane, and lignosulfonate. The test sections are subjected to climatic actions only as neither traffic nor surface courses are applied. With the investigation covering two years, the layers’ stiffness, deformation, and resistance to penetration are evaluated by employing a light-weight deflectometer and dynamic cone penetrometer. Both organosilane and lignosulfonate significantly enhance the mechanical properties of the treated base layers.